High-skilled migration in times of global economic crisis - Czaika, M; Parsons, C (International Migration Institute, 2016)
We introduce two pioneering databases in order to analyze the implications of the Global Economic Crisis on international migration. The first details inflows of migrant workers of 185 nationalities to 10 OECD destinations, disaggregated by skill level (highly skilled and otherwise), between 2000 and 2012. The second comprises immigration policies implemented by 19 OECD countries between 2000 and 2012. We distinguish between six skill-selective admission policies, six post-entry policy instruments and three bilateral agreements. Subsequently we present preliminary analysis of these data against the backdrop of the Global Economic Crisis. The Global Economic Crisis negatively affected annual inflows of both highly and other skilled migrants between 2007 and 2009, although they resumed their upward trend thereafter. The starkest trends in policy terms include: the emergence and rapid diffusion of student job seeker visas, the relative stability in the prevalence of skill selective policies in the wake of the Global Economic Crisis, a greater use of financial incentives to attract high-skilled workers and increased employer transferability for migrants at destination.